Thư viện với mục tiêu phát triển bền vững - Phạm, Kim Thanh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Library can make a major contribution to the achievement of the Sustainable Development Goals as well as the United Nations Millenial Development Goals of each country. Its roles and responsibilities have been identified in the 2030 Agenda for Sustainable Development annouced by the United Nations in September 2015. Library provides information, exchanges knowledge, improves human interlectual as well as the cultural and spiritual life of each citizen. It also provides people equal access to information and creates an enormous amount of information for humankind. Library services and products contribute to the achievement of the sustainable development goals of each country as library is considered the bridge to provide information, to promote and advertise about United Nations sustainable development goals, Millenial Development Goals.